Common haematological malignancies in Northeastern Nigeria: a multi-centre study of their pattern, distribution and treatment challenges - Dachi, Rufai Abdu; Mustapha, Falmata Grema; James, Jesini; Pindiga, Kasim Muhammad; Ezenkwa, Uchenna Simon; Yusuf, Maimuna Orahachi; Yuguda, Saleh; Suleiman, Dauda Eneyamire (Frontiers in Oncology, 2025)
BackgroundHaematological malignancies (HMs) are primary cancers of the blood and blood-forming organs. They are heterogeneous and of diverse clinical features, treatment protocols and prognoses. They constitute a significant source of cancer-related morbidity and mortality. Northeastern Nigeria, being the region in the country with the worst literacy rate and poverty indices, is also battling with the burden of these diseases with the limited health facilities to adequately diagnose and treat these ailments. There is paucity of a comprehensive data on HMs in the region, so this study aims to report on the multi-centre burden of the common HMs in the region and to discuss their patterns of distribution and management challenges.Materials and methodsThis was a 5-year retrospective study where records of cases of HMs diagnosed in the four health facilities [viz., Abubakar Tafawa Balewa University Teaching Hospital (ATBUTH), Bauchi; Federal Teaching Hospital (FTH), Gombe; Modibbo Adama University Teaching Hospital (MAUTH), Yola; and Federal Medical Centre (FMC), Azare] were collected from 1 January 2018 to 31 December 2022. Data on the age, gender, diagnosis and subtypes of some malignancies were also obtained and analysed using the SPSS Version 23.0 statistical software.ResultsA total of 493 cases of HMs, which constituted 8.2% of all cancers, were diagnosed during the period under review. Paediatric HMs constituted 42.0% (207/493) of the HMs. Non-Hodgkin lymphoma (NHL) constituted the majority of the HMs at 115/490 (23.5%), while multiple myeloma (MM) was the least at 38/493 (7.7%). An average cost of 5,000 to 10,000 United States dollars is required to manage an HM in Nigeria. Late presentation of patients, non-availability and inadequate number of personnel, inability to pay for investigations and/or treatments due to financial constraints, and limited facilities for tests such as flow cytometry, immunohistochemistry, cytogenetic and molecular genetic analyses were the challenges identified in the institutions in Northeastern Nigeria that manage cancer patients.ConclusionHaematological malignancies are common in our environment, and there are limited facilities and expertise to accurately diagnose and treat them in the region and Nigeria in general.